Utilização do resíduo líquido de indústria de processamento de suco de laranja como meio de cultura de Penicillium citrinum: depuração biológica do resíduo e produção de enzima - Tavares, Valquíria Barco [UNESP]; Sivieri, Kátia [UNESP]; Ceron, Carlos Roberto [UNESP]; Silva, Roberto da [UNESP]; Trabuco, Elizeu [UNESP]; Lombardi, Fábio Renato [UNESP]; Gomes, Eleni [UNESP] (Sociedade Brasileira de Química, 1998)
Penicillium citrinum grown in orange juice processing wastes medium under continuous agitation was studied in order to establish optimal conditions (incubation period, incubation temperature, initial pH and nitrogen addition) for biomass and ribonuclease production, as well as, biological depuration of the wastes. Nitrogen addition to wastes medium increased the biomass and ribonuclease production and provides COD reduction. The soy meal shows to be the best nitrogen source. The conditions for a more favorable enzyme and biomass production and COD reduction were initial pH 6.0 and temperature of 27°C. The maximum value obtained for these parameters on optimal conditions of cultivation was 11 U/mL of enzyme, 4 mg/mL of biomass (dry matter) and 55% of COD reduction, in 96 hours of incubation.
Utilization of residual liquid orange from juice processing as cultivation medium of Penicillium citrinum: biological depuration of the residue and enzyme production
Keywords: wastes; fungal grown; COD